Market Development Strategies for the Florida Tropical Fruit Industry - Robert L. Degner; Susan D. Moss; Jonathan H. Crane (EDIS)
The extensive fieldwork required for this project was began in 1994 and was completed in early 1996. Because of tropical fruit grower and shipper interest, results of the on-going research were released piecemeal through several conferences, associated proceedings, journal articles, and a draft report in mid-1996. These materials, submitted to the Florida Department of Agriculture and Consumer Services and the USDA's Federal State Market Improvement Program (FSMIP), met the required reporting requirements. This report has been prepared to fill the continuing need for one comprehensive reference covering all phases of this tropical fruit marketing research.